Brain natriuretic peptide in acute myocardial infarction: a marker of cardio-renal interaction. Issue 11 (November 2016) - Moltrasio, Marco; Cosentino, Nicola; De Metrio, Monica; Rubino, Mara; Cabiati, Angelo; Milazzo, Valentina; Discacciati, Andrea; Marana, Ivana; Bonomi, Alice; Veglia, Fabrizio; Lauri, Gianfranco; Marenzi, Giancarlo
Abstract : Aims: Cardiac and renal functions are major independent predictors of outcomes in both ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI). As B-type natriuretic peptide (BNP) seems to be a major mediator in the cross-talk between heart and kidneys, we aimed at evaluating its capacity to reflect cardiac and renal function in patients with STEMI and NSTEMI. Methods: We measured BNP plasma levels at hospital admission in 619 patients with STEMI ( n = 346) and NSTEMI ( n = 273), grouped according to left ventricular ejection fraction (LVEF; > or ⩽40%) and estimated glomerular filtration rate (eGFR; > or ⩽ 60 ml/min/1.73 m 2 ). Results: Median BNP values were 82 (38–186), 121 (40–342), 219 (80–685), and 474 (124–1263) pg/ml in patients with normal LVEF and eGFR ( n = 347), with LVEF 40% or less and eGFR higher than 60 ml/min/1.73 m 2 ( n = 120), with LVEF higher than 40% and eGFR 60 ml/min/1.73 m 2 or less ( n = 86), and with combined LVEF and eGFR reductions ( n = 66), respectively ( P < 0.0001). At general linear model, both LVEF higher than 40% ( P < 0.0001) and eGFR 60 ml/min/1.73 m 2 or less ( P < 0.0001) independently predicted BNP values. At multivariable analysis, BNP, LVEF 40% or less, and eGFR 60 ml/min/1.73 m 2 or less were found to be independent predictors of the combined end point of in-hospital death, cardiogenic shock, need for renal replacement therapy, or mechanical ventilation ( P = 0.003; P < 0.0001; P = 0.01, respectively). Conclusion: BNP plasma levels are closely related to LVEF and eGFR at hospital admission, in both STEMI and NSTEMI patients. Future studies should investigate whether BNP levels can summarize in a single parameter the prognostic information provided separately by cardiac and renal dysfunction.